2012
DOI: 10.1111/j.1471-1842.2012.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Do quality improvement systems improve health library services? A systematic review

Abstract: Background: A turbulent financial and political climate requires health libraries to be more accountable than ever. Quality improvement systems are widely considered a 'good thing to do', but do they produce useful outcomes that can demonstrate value? Objectives: To undertake a systematic review to identify which aspects of health libraries are being measured for quality, what tools are being used and what outcomes are reported following utilisation of quality improvement systems. Results: Many health librarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Papers by Hershey, Kaufman, Aabo, ALIA, Bryant and Allen were assessed as informative but of variable quality and lacking in adequate supporting evidence. Gardois, Medernach, Marshall, Gray and Sievert provided evidence of the intangible benefits or the intrinsic value of clinical libraries but did not identify relevant values or costs of service delivery. Given the recent interest in ‘value of information’ in reducing uncertainty, methods and benchmarks for evaluating ROI in relation to these benefits are emerging.…”
Section: Excluded Papersmentioning
confidence: 99%
“…Papers by Hershey, Kaufman, Aabo, ALIA, Bryant and Allen were assessed as informative but of variable quality and lacking in adequate supporting evidence. Gardois, Medernach, Marshall, Gray and Sievert provided evidence of the intangible benefits or the intrinsic value of clinical libraries but did not identify relevant values or costs of service delivery. Given the recent interest in ‘value of information’ in reducing uncertainty, methods and benchmarks for evaluating ROI in relation to these benefits are emerging.…”
Section: Excluded Papersmentioning
confidence: 99%
“…Twenty-one studies that reported on quality assessment in the methods section referenced the tools or aids used: 14 studies reported using one aid, four studies reported using two aids, and three studies used three or more aids (see table 3). Seven studies modified the aids (see table 2), but in four of these studies (Beverley, Bath, & Booth, 2004;Brettle, 2007;Brettle et al, 2011;Gray, Sutton, & Treadway, 2012) what modifications were made is unclear. Four studies reported using bespoke (i.e.…”
Section: Quality Assessment Toolsmentioning
confidence: 99%
“…Thus, the systematic reviews were either unclear about which of the included studies met each of the criteria assessed, or the systematic reviews were unclear about what criteria was used to assess the included studies. Two studies reported only criteria relating to the validity and reliability of the outcome tool (Ankem, 2005;Ankem, 2006a) while one study failed to report on all studies in the quality assessment (Gray et al, 2012). The remaining 14 studies were assessed as unclear as they did not report on quality assessment of the included studies in the results section of their review.…”
Section: Prisma Assessmentmentioning
confidence: 99%
“…In this issue breadth of the Health Information and Libraries Journal we are pleased to publish contributions originating from Canada, South Africa, the United Kingdom, and the United States of America …”
Section: In This Issue…mentioning
confidence: 99%